Predicting outcomes in traumatic out-of-hospital cardiac arrest: The relevance of Utstein factors - Beck, B.; Bray, Janet; Cameron, P.; Straney, L.; Andrew, E.; Bernard, S.; Smith, K. (BMJ Publishing Group, 2017)
Background: Given low survival rates in cases of traumatic out-of-hospital cardiac arrest (OHCA), there is a need to identify factors associated with outcomes. We aimed to investigate Utstein factors associated with achieving return of spontaneous circulation (ROSC) and survival to hospital in traumatic OHCA. Methods: The Victorian Ambulance Cardiac Arrest Registry (VACAR) was used to identify cases of traumatic OHCA that received attempted resuscitation and occurred between July 2008 and June 2014. We excluded cases aged < 16 years or with a mechanism of hanging or drowning. Results: Of the 660 traumatic OHCA patients who received attempted resuscitation, ROSC was achieved in 159 patients (24%) and 95 patients (14%) survived to hospital (ROSC on hospital handover). Factors that were positively associated with achieving ROSC in multivariable logistic regression models were age =65 years (adjusted OR (AOR)=1.56, 95% CI: 1.01 to 2.43) and arresting rhythm (shockable (AOR=3.65, 95% CI: 1.64 to 8.11) and pulseless electrical activity (AOR=2.15, 95% CI: 1.36 to 3.39) relative to asystole). Similarly, factors positively associated with survival to hospital were arresting rhythm (shockable (AOR=3.92, 95% CI: 1.64 to 9.41) relative to asystole), and the mechanism of injury (falls (AOR=2.16, 95% CI: 1.03 to 4.54) relative to motor vehicle collisions), while trauma type (penetrating (AOR=0.27, 95% CI: 0.08 to 0.91) relative to blunt trauma) and event region (rural (AOR=0.39, 95% CI: 0.19 to 0.80) relative to urban) were negatively associated with survival to hospital. Conclusions: Few patient and arrest characteristics were associated with outcomes in traumatic OHCA. These findings suggest there is a need to incorporate additional information into cardiac arrest registries to assist prognostication and the development of novel interventions in these trauma patients.